Utilization of Local Microorganisms (MOL) as Organic Fertilizer in Women's Farmer Group, Sanur Kauh Village, Denpasar - Rukmini, Ni Ketut Sri; A.A. Sagung Putri Risa Andriani (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2022)
The partner in implementing this community service program (PKM) is the Farmer Group located in Sanur Kauh Village, South Denpasar District, Denpasar. The group is cultivating organic plants by utilizing organic waste such as dry leaves, household waste, canangg residues (waste from Hindus Bali ritual events) , and cow and chicken manure. The group does not yet know how to properly process organic waste to produce good organic fertilizer. During this time, the garbage is just piled up just like that, and let the decomposer process takes place naturally. The group also does not know the proper composition of organic waste so as to produce a complete organic fertilizer containing NPK nutrients. The method that will be carried out in the implementation of this training is by interviewing, face-to-face methods, counseling and direct practice, Gradually the activity will be carried out: First, we will hold counseling on the use of local microorganisms as organic fertilizers. Second, we will provide direct training on the use of local microorganism (MOL), carried out several evaluations The third time, if the PKM activity will end we will motivate farmers so that in growing vegetables such as lettuce, kale, green vegetables and long beans by applying the use of MOL as organic fertilizer. From this activity, the external target to be achieved is that training participants understand how to use MOL as organic fertilizer to get healthy organic vegetables. The women's farmer group was able to make MOL which was used as a physically quality liquid organic fertilizer. Partners by 70% understand and can apply liquid organic fertilizer from household waste. Partners were able to reduce production costs by 25%, partners were able to reduce organic waste that causes environmental pollution by 80%, and partners were able to increase crop production by 25% thereby increasing group profits